THE NEED TO REFORM ORGANIZATIONAL AND MANAGEMENT MECHANISMS IN HIGHER EDUCATION INSTITUTIONS AND IMPLEMENT NEW PRINCIPLES TO THEM (Scientific journal of the Fergana State University, 2024)
In this article, the training of qualified and competitive personnel in the higher education system is an urgent socio-economic issue, and the introduction of new approaches to the organization and management of educational activities in the higher education system, personnel training and continuous education system, the dynamics of development and structural changes of state and non-state educational institutions are expressed.